Dharma ratna prakaraṇa : mūla ane Gujarātī bhāṣāntara - Devendrasūri, 13th cent (Śrī Jaina Dharma Vidyā Prasāraka Varga, 1906)
Prakrit text, with Sanskrit and Gujarati translation and commentary on Jaina Doctrines.